PROBLEMATIKA PEMERINTAH DALAM MENYONGSONG BONUS DEMOGRAFI DI INDONESIA - Isyana Kurniasari Konoras; Tria Anggraini Wagiran; Syaifullah Mukhlis (Institut Agama Islam Negeri (IAIN) Manado, 2018)
Abstract. Demographic bonuses are a hot issue, although they are still limited to population and economic experts, even among other academics the term bonus demography is still not well known. The study has not reached a legal perspective. Some aspects related to the demographic bonus are the implementation of the Sustainable Development Goals (SDGs) until 2030. While the prediction of achieving demographic bonuses by Indonesia in 2020-2030. The series of periods of achieving the demographic bonus, in the analysis of population experts including economists, still